La crítica argentina de arte destinada a públicos masivos. 2° etapa: estilos críticos entre 1912 y 1940 - Proyecto - Petris, José Luis (2015)
The project is a continuation of the first stage, already concluded, in which a first scheme of periodization for the history of Argentine art criticism destined to mass audiences in the twentieth century was built. In this second stage we propose ourselves to, first of all, initiate the testing of the periodization achieved and, secondly, to perform the description and analysis of critical styles of the first period, between 1912 and 1940. Non-specialized art criticism is mediator between art and society and an instrument of legitimation for art outside its specific field of performance, and has consequences both direct and indirect for its aesthetic and poetic developments. However, despite its political importance, it doesn’t have so far in our country the systematic study it requires, until now. The research aims to achieve results that could provide and encourage work on this postponed subject of study, key to the history of Argentine art.